Basaloid Squamous Cell Carcinoma of the Uterine Cervix: Report of a Case With Molecular Analysis. (October 2021) - Munkhdelger, Jijgee; Shimooka, Tomoko; Koyama, Yoshinori; Ikeda, Sadakatsu; Mikami, Yoshiki; Fukuoka, Junya; Hori, Takashi; Bychkov, Andrey
There is a lack of knowledge about molecular alterations in basaloid squamous cell carcinoma (BSCC) of the uterine cervix. A 72-year-old woman with a history of previous subtotal hysterectomy and current vaginal bleeding was referred to our hospital. Initially, adenoid cystic carcinoma (ACC) was diagnosed upon cervical cytology and biopsy. Chest imaging showed multiple metastatic lesions in both lungs. The surgical specimen showed BSCC with diffuse p16 immunoreactivity and negativity for S-100, c-kit, and neuroendocrine markers. There was a focal minor ACC component, which could have explained the previous cytology and biopsy diagnosis. Next-generation sequencing with two different panels showed coexisting PIK3CA mutation and NTRK2 fusion with 10 additional variants of unknown significance ( ATR, DAXX, FAM123B, JAK1, KEL, MLL2, NOTCH2, PALB2, POLD1, POLE ). The MYB gene fusions were not identified. The patient received chemotherapy with TRK inhibitor larotrectinib and carboplatin, which caused shrinkage of metastatic lung nodules. This is the first report of cervical BSCC with extensive molecular workup, which detected multiple genetic events, including targetable ones, which are potentially implicated in the development of a tumor. The accumulation of data and further studies on this tumor are necessary to define its diagnostic criteria and its clinical and biological behavior.